Effect of Double Interior Stiffeners on the Flexural Behavior of Concrete Filled Steel Tube Composite Box Girders - Abedi, Hussam Aldin O.; Rasheed, Mohammed M. (Engineering, Technology & Applied Science Research, 2023)
A composite box girder is a type of structural element that possesses strong torsional stiffness and resistance against flexural forces. A new category of bridge structure has been established: one that consists of concrete-filled steel tubes connected to composite slabs by steel trusses. In this study, an experimental and computational analysis of flexural loadings on four different types of composite box girders that are connected to concrete-filled steel tubes is presented. The specimens in this test are subjected to a concentrated load at the span’s midpoint. The first model is a concrete-filled tube with no internal stiffeners and is used as a control specimen. The second model is a concrete-filled tube with double internal I-shaped stiffeners welded inside a steel tube. The third model features double T-shaped stiffeners, and the fourth model features stiffeners in the shape of a V. When compared with the control specimen, the results of the tests demonstrated that the Concrete-Filled Steel Tube (CFST) section equipped with internal stiffeners provided a better strength capacity and exhibited less deflection. The I- and the V-shaped stiffeners were found to be inferior to the T-shaped. The findings of the numerical analysis were in accordance with the results of the test.